DETERMINAN’S OF PURCHASING INTENTION IN TIKTOK SHOP E-COMMERCE: THE ROLE OF DIGITAL MARKETING AND FINANCIAL LITERACY IN SAMARINDA - Tiara Almira Pratiwi; Poppy Alvianolita Sanistasya; Mukhibatul Hikmah; Ummi Nadroh (BEMJ : Business, Entrepreneurship, and Management Journal, 2025)
This study investigates the influence of Affiliate Marketing, Financial Literacy, and Online Customer Ratings on consumers’ Purchase Intention within the TikTok Shop e- commerce platform in Samarinda, Indonesia. Amidst the rapid growth of online shopping behavior through social media, TikTok Shop has emerged as a prominent platform, particularly among younger demographics. Employing a quantitative research approach, data were collected from 100 active TikTok Shop users via an online questionnaire. The analysis was conducted using SPSS version 22 and applied multiple linear regression techniques. The findings reveal that, individually, both Affiliate Marketing and Online Customer Ratings exert a positive and statistically significant impact on consumers’ Purchase Intention. Conversely, Financial Literacy does not exhibit a significant partial effect. However, when analyzed simultaneously, all three variables Affiliate Marketing, Financial Literacy, and Online Customer Ratings demonstrate a significant collective influence on Purchase Intention. These results underscore the strategic importance of digital marketing content and credible customer feedback in enhancing consumer engagement and purchase decision-making on social commerce platforms like TikTok Shop. This research contributes to the growing literature on digital consumer behavior and offers practical insights for e-commerce practitioners aiming to optimize affiliate-based marketing strategies and manage user-generated reviews effectively to align with evolving consumer expectations.